2000
DOI: 10.1677/joe.0.1660621
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a role for neuropeptide Y and monoamines in mediating the appetite-suppressive effect of GH

Abstract: Among the many responses to GH administration is suppression of voluntary feed intake (FI) in some species, attributed to improvement in the efficiency of nutrient utilization and, therefore, reduced need for ingested substrates. Commercial broiler chickens have been genetically selected for generations for rapid growth, realized largely via the major correlated response of increased voluntary feed consumption. Neuropeptide Y (NPY) and monoamines play very important roles in the central regulation of feeding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition, GH alters appetite and feeding behavior (20). It is not known whether these effects occur outside or within the BBB, and if inside, whether by direct action or indirect alteration of other neurotransmitters in response to GH.…”
mentioning
confidence: 99%
“…In addition, GH alters appetite and feeding behavior (20). It is not known whether these effects occur outside or within the BBB, and if inside, whether by direct action or indirect alteration of other neurotransmitters in response to GH.…”
mentioning
confidence: 99%
“…Noteworthy is the observation of the diminution of body fat levels due to GH administration despite the increase in feed intake. Previous studies have demonstrated that the effect of GH on food intake is species, age and sex dependent ( 49 , 50 ) . Our own study shows that GH administration diminished body fat levels in all animals independently of age and sex, and paradoxically there was an increased feed intake in adult mice and to a greater magnitude in males than in females, suggesting important effects of sex and ageing hormone regulation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings, together with our results, suggest that the higher mRNA level of hypothalamic NPY in the layer-type chicken is due to increased behaviors, including feeding behaviors. On the other hand, growth hormone inhibits the hypothalamic NPY in chickens (Wang et al, 2000), and the peak of growth hormone secretion appears at the age of 14~28 d (Burnside and Cogburn, 1992). Body weight of the meat-type chicken was significantly greater than that of the layer-type chicken at the same age, suggesting a rapid growing rate in the meat-type chicken.…”
Section: Discussionmentioning
confidence: 99%